The language of humour - Nash, Walter 1926-2015 (Routledge, 2013)
The broad aim of this lively and engaging book is to examine relationships between the linguistic patterns, the stylistic functions, and the social and cultural contexts of humour. The material used in illustration is of corresponding breadth: schoolyard jokes, graffiti, aphorisms, advertisements, arguments, anecdotes, puns, parodies, passages of comic fiction, all come under Dr Nash's scrutiny
Keywords: English wit and humor / History and criticism; English language / Style; Literary style; Comic, The; HUMOR / General; English wit and humor; Electronic books; Criticism, interpretation, etc